Analysis Towards Stock Price With Earnings Per Share As Moderating Variable - Ivan Aditya Nugraha; Nurul Fadila; Nurhana Dhea Parlina (CV. AFDIFAL MAJU BERKAH, 2024)
Most countries in the world are haunted by 2023 economic recession. Indonesia economic growth also slowed to 5,40% in 2022. This issue threatens some sectors, especially financial. This study's purpose is to see the bank subsector companies’ financial performance listed on the IDX from 2020 until 2022. Since banks require debt capital to run their operations, The stock price is the dependent variable in this research, yet the independent variables are DER and ROE, and earnings per share is the moderation. The data is processed using STATA and panel data regression analysis through the Random Effect Model. The research result shows that if DER partially increases, the stock price does not increase significantly. Meanwhile, if ROE partially increases, so does the stock price. Share prices will follow an increase in ROE and DER simultaneously, but after being moderated by EPS, an increase in DER will be followed significantly by stock value. However, an increase in ROE moderated by EPS is not necessarily followed by an increase in share price, while an increase in DER and ROE after being moderated by EPS will have effect on share value.